The american journey : - Appleby, Joyce (Glencoe/McGraw-Hill, 2000)
The American Journey: Building a Nation is co-authored by the National Geographic Society and offers a unique blend of scholarship and compelling imagery. The hands-on learning approach used throughout the program helps students see the relevance of history as they discover the context and connections between historical events. The program offers in-depth coverage of America's past to 1914. A visual epilogue then brings students up to date.